Xenogeneic equine stem cells activate anti-tumor adaptive immunity in a 4T1-based intraductal mouse model for triple-negative breast cancer: proof-of-principle - Steenbrugge, Jonas; Pauwelyn, Glenn; Demeyere, Kristel; Devriendt, Nausikaa; de Rooster, Hilde; Sanders, Niek N.; Spaas, Jan H.; Meyer, Evelyne (Frontiers in Immunology, 2023)
Triple-negative breast cancer (TNBC) remains difficult to treat, especially due to ineffective immune responses. Current treatments mainly aim at a cytotoxic effect, whereas (stem) cell therapies are being investigated for their immune stimulatory capacities to initiate the antitumor immunity. Here, a thoroughly characterized, homogenous and non-tumorigenic mixture of equine mesenchymal stem cells (eMSCs) harvested from horse peripheral blood as innovative xenogeneic immunomodulators were tested in a 4T1-based intraductal mouse model for TNBC. The eMSCs significantly reduced 4T1 progression upon systemic injection, with induction of inflammatory mediators and T-cell influx in primary tumors, already after a single dose. These xenogeneic anti-cancer effects were not restricted to MSCs as systemic treatment with alternative equine epithelial stem cells (eEpSCs) mimicked the reported disease reduction. Mechanistically, effective eMSC treatment did not rely on the spleen as systemic entrapment site, whereas CD4 + and CD8α + T-cell infiltration and activation were critical. These results show that eMSCs and potentially also other equine stem cell types can be a valuable TNBC treatment strategy for further (pre)clinical evaluation.